Analisis Strategi Pemasaran Dan Hasil Penjualan Pada UMKM Keisha Jaya Pace Di Masa Pandemi Covid-19 - Rivan Aji Setiawan; Bambang Suwarsono; Umi Nadhiroh (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This thesis aims to find out what are the marketing strategies and results during the Covid-19 pandemic at MSMEs Keisha Jaya Pace and efforts to improve the marketing and sales strategies of MSMEs Keisha Jaya Pace during the Covid-19 pandemic. This study uses descriptive qualitative research. Data collection methods in this study using interviews, observation, documentation. Test the validity of the data in this study using Triangulation. The data analysis method in this study uses a data redcution model, data presentation, conclusion drawing. The results of this study indicate that the marketing strategy of Keisha Jaya Pace MSMEs during trhe Covid-19 pandemic experienced difficulties when implementing marketing strategies. Keisha Jayya Pace MSMEs implement a marketing mix including product, price, place, and promotion strategies. The sales results of Keisha Jaya Pace MSMEs during the Covid-19 pandemic experienced a decline in sales. Almost all Keisha Jaya Pace MSMEs product experienced a decline in sales, including diamonds, jenang, kembang gulo, cum-cum cakes due to the implementation of the Emergency PPKM and work from home. There are several efforts of Keisha Jaya Pace MSMEs in increasing sales during this pandemic, including providing the best service to consumers, aggressively promoting products on social media, paying attention to product quality standards, and maintaining good relationships with buyers.